Specialist service for the provision of opthalmic benefit (circular) - Harwood, E. G.
1929-01 1929 1920s 8 pages NATIONAL OPHTHALMIC TREATMENT BOARD. THE SECRETARY, 1 High Street, Marylebone, W.1. January 1929, SIR, I am directed by the National Ophthalmic Treatment Board to enclose herewith particulars of a Specialist Service for the provision of Ophthalmic Benefit as an additional benefit under the National Health Insurance Acts and to enquire whether you are desirous of utilising the service for the benefit of your members. It is common knowledge that Approved Societies are not wholly satisfied with the present system of administering ophthalmic benefit and that they recognise that the utilisation of the services of opticians for the purpose of testing sight is directly opposed to the report of the Royal Commission on National Health Insurance, which recommended the establishment of an ophthalmic specialists' service for the treatment of insured persons, and that the function of the optician should be restricted to the provision of the glasses prescribed by the eye specialist. The recent Majority Report of the Committee appointed by the Minister of Health to consider the Optical Practitioners' Bill also remarked under the heading "The Ideal Form of Treatment" that "It is generally agreed that in the best interests of the patient the examination of his eyes should if at all possible be carried out by an oculist." Approved Societies, however, while anxious to secure for their members the best form of ophthalmic treatment have hitherto been unable to do so owing in the main to the relatively high cost of securing the services of an ophthalmic surgeon, and to a minor extent to the lack of an efficient organisation acting under his direction. The service described in the appendix to this letter, while carrying out in a complete and practical form the recommendation of the Royal Commission on this subject, compares very favourably in the matter of cost with the existing scheme administered by the Joint Council of Qualified Opticians. Under the J.C.Q.O. Scheme, Approved Societies pay a general maximum of 15s. 6d. for testing and the provision of glasses. Complaint is frequently made by the patient of the inferior quality frames and lenses provided for this sum, and in approximately 90 per cent. of cases at the present time the member prefers to pay an additional sum to obtain better quality frames with a better appearance. The existing scheme moreover is open to abuse in view of the opportunity which exists for variation with regard to the prices charged for other than "utility" glasses, and it depends entirely upon the cupidity of the individual sight testing optician as to what amount the members are required to pay, the quality of the lenses and framework supplied, and the care and accuracy displayed in dispensing and fitting. Approved Societies also, under the existing scheme have great difficulty in checking the accounts sent in by reason of the varied charges for different powers of lenses. There is no definite line of demarcation easily understood by non-technical persons to enable Approved Societies to determine whether certain lenses are within the limit of the price allowed, or what extra charge may be justified. These difficulties are automatically eliminated in this scheme. The provisions of this specialist service have been framed with great care to meet the varied requirements of different Approved Societies, and although it is hoped that they will meet with the approval of societies, the promoters would be prepared to consider any reasonable and practical amendments to the scheme if persuaded that such changes were generally desired by Societies and provided that they did not prejudice the other parties to the arrangement. The scheme provides for the administration of ophthalmic benefit on the basis of a fixed liability for Approved Societies, which will therefore be in a position to estimate their expenditure in respect of this additional benefit with very much greater accuracy — an important consideration. By virtue of the extreme simplicity of the scheme moreover societies will be able to reduce their administration expenses to an absolute minimum. 1 292/841.4/1/58